Tapering: critical review - Anderson, O.
Athletes are gradually getting the idea that reducing their training ('tapering') prior to major competitions is a good idea, but major disagreements about exactly how to taper remain. There's considerable debate about whether one should reduce training volume (mileage or time) while preserving training intensity (speed) during a tapering period, trim intensity while maintaining volume, or simply cut back on both. There are also differences of opinion concerning how often one should train (frequency), how long the tapering period should actually last, and whether different competitive events require dissimilar tapers.